QUALIDADE NA PERCEPÇÃO DISCENTE DO CURSO DE ADMINISTRAÇÃO - Gabriella Depine Poffo (Universidade Federal de Santa Catarina, 2013)
This study aims to identify the perceptions of students from the Faculdade AVANTIS’ Administration Course concerning educational quality of this chair, with direction by applying the Hedperf Model suggested by Firdaus (2006). As a mechanism to deepen the perception of students, the survey was split between freshmen and seniors to answer their question bases this study: Witch is the perception of students of academic administration course in relation to quality? To the realization of this proposal, the present article structure will be as follows: I) introduction referring to proposed topic and presentation of objectives; II) a brief review of the concept of quality; III) characterization of Hedperf Model, of this research instrument; IV) methodological procedures for targeting of objectives and problem question; V) results obtained through the data collected and their analysis; and, finally, VI) the final considerations of the study proposed here.